Enhancing Athlete Performance with Mobile Health Applications: Benefits and Challenges - Wahyudi, Nanang Tri; Yunus, Moch (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2025)
Introduction:Mobile health applications have gained significant attention in recent years due to their ability to enhance athletic performance, prevent injuries, and support overall health management. By integrating advanced technologies, these applications provide athletes with personalized exercise plans, real-time monitoring of physiological and psychoemotional indicators, and immediate feedback. Method:This study employed a systematic literature review (SLR) using the PRISMA framework to identify, screen, and synthesize peer-reviewed studies published between 2013 and 2023. Databases including PubMed, Scopus, and Web of Science were searched using terms such as "mobile health applications," "athlete performance," and "privacy compliance." Eligible studies focused on mobile health applications specifically designed for athletes, addressing features like personalized plans, monitoring, and data security. Results:The review identified that mobile health applications significantly improve athletic performance, injury prevention, and motivation through personalized exercise plans and real-time feedback. However, persistent challenges were noted, including difficulties in personalizing plans for diverse athletes, ensuring user adherence, and addressing privacy and security concerns related to data handling. The findings underscore the need for robust privacy mechanisms and interdisciplinary collaboration to optimize these applications. Conclusion:Mobile health applications play a vital role in enhancing athletes' physical and mental well-being. However, addressing challenges such as personalization, adherence, and data security is essential to their continued success. Future research should focus on advancing AI-driven personalization, improving user engagement, and strengthening privacy safeguards to maximize the potential of these applications in athletic health management.